Redescription of Isocondylus Amyot & Serville 1843 (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) - Del Carmen, Coscarón María; Cava, María Belén; Corronca, José Antonio (Zootaxa, 2008)
The Neotropical genus Isoncondylus, proposed by Amyot and Serville (1843) for Reduvius elongatus Lepeletier & Serville, was cataloged as a valid genus by Stål (1872), Wygodzinsky (1949), and Maldonado Capriles (1990).